Analisa Dampak Lingkungan Pada Instalasi Pengolahan Air Minum (IPAM) Dengan Metode Life Cycle Assessment (LCA) - Desrina Yusi Irawati; David Andrian (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
Babat Drinking Water Treatment Plant (IPAM Babat) is one of the clean water facilities for Lamongan community. The process of clean water requires an appropriate processing. This process requires chemicals and energy that it will adverse effects to the environment. Life Cycle Assessment (LCA) is one of the environmental effects analyze methods for clean water process. The four phases of LCA are Goal And Scope Definition, Life Cycle Inventory, Life Cycle Impact Assessment, and Interpretation. The environmental impacts of the LCA method of processing are divided into three broad categories of impacts, namely the categories of human health, ecosystem quality, and resources. The result of LCA analyzed shows that electrical energy utilization product an environment impact significantly. This impact has consequences on the resource category (fossil fuels) and human health (climate change) due to CO2 combustion. The largest electric consumption is used for tools of pumping water due to the distant length intake and IPAM. The solution for reduced the electric consumption is using the equipment efficiency and water flow system by the power of gravity.